2005
DOI: 10.1016/j.polymer.2005.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Association behavior of thermo-responsive block copolymers based on poly(vinyl ethers)

Abstract: Thermo-sensitive nanosized structures have been prepared in water from poly(methyl vinyl ether)-blockpoly(isobutyl vinyl ether) (PMVE-b-PIBVE) block copolymers. The composition and the architecture (diblock and triblock architectures) of the PMVE-b-PIBVE copolymers have been varied. The investigated copolymers had an asymmetric composition with a major PMVE block. While the PIBVE blocks are hydrophobic, the PMVE blocks are hydrophilic at room temperature and become hydrophobic above their demixing temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Support for this assumption came from several observations, including a characteristic triazole peak in the 1 H NMR (Figure S6). The acridine resonances were not observed possibly because packing of the hydrophobic chromophores within the helix leads to their reduced mobility (slow tumbling) and poor solvation. , The ligand incorporation into the polymers was established by the acridine fluorescence observed for each polymer, and particularly by UV studies that showed an approximately linear increase in absorbance with L/G feed ratio (Figure S3). The molecular weight of each polymer 4 was calculated based on the molecular weight of parent PCPLGs determined by multiangle laser light scattering (MALLS) and the alkyne loading stoichiometry (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Support for this assumption came from several observations, including a characteristic triazole peak in the 1 H NMR (Figure S6). The acridine resonances were not observed possibly because packing of the hydrophobic chromophores within the helix leads to their reduced mobility (slow tumbling) and poor solvation. , The ligand incorporation into the polymers was established by the acridine fluorescence observed for each polymer, and particularly by UV studies that showed an approximately linear increase in absorbance with L/G feed ratio (Figure S3). The molecular weight of each polymer 4 was calculated based on the molecular weight of parent PCPLGs determined by multiangle laser light scattering (MALLS) and the alkyne loading stoichiometry (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…This is possibly attributed to the higher adsorption amounts of TPC on the surfaces of cement particles. More calcium chelated complexes and more remarkable inhibition of hydration for TPC, thus resulting in the retardation of cement hydration …”
Section: Resultsmentioning
confidence: 99%
“…More calcium chelated complexes and more remarkable inhibition of hydration for TPC, thus resulting in the retardation of cement hydration. 36,37…”
Section: Setting Times Of the Cement Pastesmentioning
confidence: 99%
“…Most of the studies of temperature‐responsive polymers focus on poly( N ‐alkylacrylamide)s, poly( N ‐vinylcaprolactam) and poly(vinyl methyl ether) and their derivatives since these polymers have the peculiarity of possessing a LCST in the physiological range, which is notably important for biomedical or clothing applications. It is possible to create temperature‐responsive systems based on these polymers in the form of micelles,2–6 nanoparticles,7–9 microparticles,10–13 capsules,14–16 hydrogels,17–19 interpenetrating networks,20, 21 films and coatings22–28 and fibres 29, 30. The temperature‐responsive systems based on coatings are commercially very interesting since they require a relatively small amount of the expensive temperature‐responsive polymer to provide a significant effect.…”
Section: Introductionmentioning
confidence: 99%